Inoculatian ai cornmon beans with Xanthomanas campestris pv. phaseoli under !ieid cendilions - Faria, Josias Corrêa De; Melo, Paulo Eduardo De (Pesquisa Agropecuaria Brasileira, 2013)
Utitization of sand biasi injury for inoculation of cornmon beans (Phaseofus vulgaris L.) with Xanthomonas carnpestris pv. phaseoli under iield conditions was shown lo be highly satisfactory. Twenty- -eighl lo sixly-eight per cent of lhe total ai leaves analised with conimon blight were obtained, compared to 8% to 16% of natural incidence. Tho final disease incidence and severily obtained were 10w and not corretaled to yield. There was no difference among cultivars on the rale ol disease progress, except for 'Carioca' wilh a lower rale than 'Rio Tibagi'.